Developing Circular Economy Business Models – One of the Tools for Effectively Navigating the ESG - Gagnidze, Ineza (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
Global economic growth and intensifying international competition have led to the excessive consumption of non-renewable resources. The reviewed literature indicates that a primary challenge for effectively navigating ESG criteria is financial reporting - an issue that can be addressed through the adoption of new business models. The author proposes Circular Economy Business Models (CEBMs) as a pivotal tool in this transition. Research presented in this chapter suggests that the establishment of a circular economy (CE) is fundamentally dependent on the implementation of these models. By adopting CEBMs, individuals undergo a shift in behaviour, business vision, and values, impacting both their professional lives and their wider social and domestic environments. The author examines this issue through a systemic lens, clarifying complex interconnections. This is supported by two graphical representations: the first illustrates the links between CEBMs and ESG pillars, while the second explores the relationship between individual behavioural change and a proactive ESG-navigating attitude.